Stochastic analysis model for metro vehicle-floating slab track coupled system considering shear hinges - Fu, Weihua; Guo, Yu; Wang, Baomin (Probabilistic engineering mechanics, 2025)
To analyze the stochastic vibration characteristics of the metro vehicle-track coupled system, this paper proposed a time-varying stochastic vibration model of the metro vehicle-floating slab track system. Based on the theory of vehicle-track coupled dynamics, a vertical coupled dynamic model is developed, incorporating the shear hinge devices at the ends of the floating slab track. Simulation results shows that the shear hinge constraints effectively reduce the vertical wheel-rail dynamic interaction. Thus, car body mass, fastener stiffness, and steel spring stiffness are selected as random parameters, while the random track irregularities serve as the external excitation source for the system. Both impacts of the internal and external randomness on the vibration characteristics of the coupled system are simulated. Critical random parameter values are determined by the combination of random simulation and number theory method. The effects of different random parameters with varying variation coefficients on the vertical car body acceleration and the wheel-rail interaction force are simulated and compared. Through the probability density evolution method (PDEM), the vibration characteristics of the car body acceleration caused by random track irregularities are analyzed. The results demonstrate that the established stochastic vibration model can be used for the randomness analysis of the metro vehicle-floating slab track coupled system. The vehicle-dynamic responses indicate that running safety and riding comfort are subject to greater impact. In addition, among these random parameters, the car body mass has the most significant impact on the vehicle-track dynamic interaction. •A stochastic vibration model for metro vehicle-floating slab track coupled system.•Shear hinge devices which can reduce wheel-rail interaction are considered.•Effects of different random parameters of both vehicle and track are analyzed.•PDEM is applied to vibration analysis caused by random track irregularities.